A more Synodal Faculty and a more Prophetic Theology. Theology and Faculty in an "Ecclesia semper reformanda" (Teología, 2018)
In this Lectio Inauguralis the Dean propose to think of ways towards a more synodicalfaculty and a more prophetic theology. Synodality and prophecy are clues that includemany institutional and theological questions. They reframe the historical figure of theinstitution and the balances in theological thinking.The “more” double (magis) points to the challenge of taking steps towards newgoals, which means going from one less to another according to a metaphysics ofparticipation, a theology of conversion, reformation or purification, and a pathspirituality . The melius of a change aims to improve the good that exists. A positivechange is a mutatio in melius. Saint Thomas teaches that reforms are orientedtowards the best: in melius reformantur (ST I, 45, 1, ad 1um). He adds: “changesare specified and dignified not by their term a quo but by their term ad quem”(ad 2um). In each historical moment we must discern goals, projects, processes,reforms.
Keywords: Faculty; Reform; Prophetism; Synodality; Theology